Student Learning Activity in Arabic Language Learning Reviewed from Students' Perceptions of Arabic Language Teachers - Halma Irawan; Moch. Bahak By Udin Arifin (Fitrah, 2026)
This study aims to describe students' learning engagement in Arabic language learning and examine the factors influencing it based on students' perceptions of their Arabic teachers. This research employed a qualitative approach using observation and interviews as data collection techniques. The data were analyzed using the interactive model of Matthew B. Miles and A. Michael Huberman, which includes data reduction, data display, and verification. Data validity was ensured through source and technique triangulation. The findings revealed that students' learning engagement at MTs Nurul Mi'raj Ndewel varied across different indicators. Based on students' perceptions of their teachers, several factors influencing learning engagement were identified, including interaction management, clarity of teacher explanation, task assignment and guidance, use of learning media, and equal participation in group discussions. The study concludes that understanding students' perceptions can serve as an evaluation tool for teachers to improve instructional strategies in order to enhance students' learning engagement.